Effect of L-thyroxine on bone biomechanical and morphometric parameters in rats - Sedat Aydoğdu; Reyhan Rabia Kök; Kamil Beşoluk (BMC Veterinary Research)
Abstract Background Morphometric measurements and biomech anical tests are very crucial in determining the effects of drugs and chemicals on bones. L-thyroxine is often used instead of thyroid hormone in research conducted on experimental animals. The aim of the study is to examine the effects of L-thyroxine on the morphometric and mechanical properties of rat bones. A total of 16 healthy male Wistar Albino rats were used, including control and L-thyroxine groups. After the experimental process, the left/right humerus and femur were resected from all animals. Morphometric measurements were performed on the bones. Then, three indices of the bones were calculated using the measurement results. Three-point bending was performed to determine the effect of L-thyroxine on the mechanical properties of the bones. Results Humerus maximum length and proximal width difference was determined. The maximum length and proximal width of the right humerus were lower in rats that received L-thyroxine. Differences were observed in the weight, diaphysis diameter and weight/length index of the right femur. These parameters were higher in the control group. No statistical difference was detected between L-thyroxine and control groups in mechanical properties. Maximum loading, stiffness, strength and elastic modulus in the humerus were observed to be higher in the control group. However, stiffness, strength and elastic modulus in the femur were determined to be higher in the L-thyroxine group. According to the correlation between the mechanical properties of bones and conventional indices, a high correlation was found between elastic modulus and weight/length index in the humerus. In the femur, a high negative correlation was observed between maximum loading and the weight/length index. Conclusion This study showed that L-thyroxine had an effect on the morphometry of long bones in rats but did not affect their mechanical properties. L-thyroxine has been observed to mainly affect the bones in the right side of the body.